ADULT BASIC LIFE SUPPORT ON NEAR DROWNING AT THE SCENE - Prawedana, Gd. Harry Kurnia; Suarjaya, Putu Pramana (E-Jurnal Medika Udayana, 2013)
Indonesia is a popular tourist destination which has potential for drowning cases. Therefore, required knowledge of adult basic life support to be able to deal with such cases in the field. Basic life support in an act to maintain airway and assist breathing and circulation without the use of tools other than simple breathing aids. The most important factor that determines the outcome of drowning event is the duration and severity of hypoxia induced. The management of near drowning at the scene include the rescue of victim from the water, rescue breathing, chest compression, cleaning the vomit substances which allowing blockage of the airway, prevent loss of body heat, and transport the victim to nearest emergency department for evaluation and monitoring.
Keywords: basic life support, near drowning, resuscitation